Analisis sisa umur rencana Jalan Baturinggit di wilayah Kubu Karangasem akibat adanya beban berlebih - Kadek Yoga Praba Desa; Anak Agung Gede Sumanjaya; Cokorda Agung Yujana (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2024)
Baturinggit Road is one of the main routes for shipping goods/materials involving overloaded vehicles. The more vehicles that pass, the greater the load that passes through the road, resulting in road damage. The purpose of this study was to analyze the remaining life of the road design caused by overloaded vehicles. The study was conducted for 3 days, starting from April 15, 2024 - April 17, 2024 at 08.00 WITA - 18.00 WITA on the Baturinggit Road section, Kubu District, Karangasem Regency, Bali Province. Based on the results of the study, it is known that the cumulative Vehicle Damage Factor (VDF) of normal loads during the 10-year Remaining Life (RL) is 10,658,570 ESAL while the cumulative VDF of excess loads during the 10-year RL is 28,727,670 ESAL. Based on calculations using the AASHTO 1993 method, the magnitude of the RL decrease that occurred was 291%, meaning that there was a decrease in RL of 7.45 years so that the percentage of cumulative VDF increase due to overloading was 169.53%. The percentage of vehicles with overloading that caused damage on the Baturinggit Road section included pickup trucks of 30%, light trucks of 59.80%, medium trucks of 119.52%, heavy trucks of 10% and 1.2-2 trailer trucks of 19.08%. The conclusion from the calculation results of the AASHTO 1993 method was a decrease in RL of 291% or equivalent to a loss of road life of 7.45 years from the initial design life. The impact of overloading on medium trucks is the focus of attention because of its very significant contribution to road damage.